Optimal Dispatch of the Energy Demand in Electrical Distribution Grid with Reserve Scheduling - Dwijendra, Ngakan Ketut Acwin; Anupong, Wongchai; Althahabi, Ahmed Majed; Abdulameer, Sabah Auda; Al-Azzawi, Waleed Khalid; Jaber, Mustafa Musa; Zahra, Musaddak Maher Abdul; Al Mashhadani, Zuhair I. (Environmental and Climate Technologies, 2023)
The operation of the electrical systems is a major problem for electrical companies’ subject to uncertainties threatening. In this study, the optimal management of the energy demand in the electrical distribution grid is done by interval optimization approach under electrical price uncertainty. The management of the energy demand is implemented via incentive-based modelling of the demand response programs (DRPs). The incentive-based modelling as reserve, and based on bid price for reduction of the electrical demand at peak hours is proposed. The interval optimization approach is used for the minimization of the electrical price uncertainty effects. The main objective in the proposed approach is minimizing operation cost; epsilon-constraint method is utilized to solve the problem. Finally, an electrical distribution grid has been used at various case studies to numerical simulation results and positive effects of the proposed modelling under uncertainties.